The Effect of the Google Classroom-Based Flipped Model on the Learning Outcomes of Machinery Theory in the Covid-19 Pandemic - Muslim, Muslim; Basuki, Nur; Marlan, Marlan; Sarwa, Sarwa (Journal of Community Research and Service, 2022)
This study investigates the implementation of the Google Classroom-based flipped classroom model for teaching machining theory during the COVID-19 pandemic in the Department of Mechanical Engineering Education, Faculty of Engineering, State University of Medan, which impedes learning activities. In accordance with the current situation and conditions of the covid-19 pandemic, an alternative and appropriate solution is required, namely the application of the flipped classroom model based on the google classroom to improve student learning outcomes in the machining theory course. The flipped classroom model can assist students in achieving learning objectives in a manner that is considered simple. Through the Flipped classroom, lecturers at the Department of Mechanical Engineering Education, Faculty of Engineering, State University of Medan can utilize online learning to facilitate students' access to and study of course materials. It is crucial to conduct research on this issue for this reason. This research has three objectives: (1) to examine the learning outcomes of students who use the flipped classroom learning model assisted by Google Classroom in the treatment class; (2) to examine the learning outcomes of students who use the conventional learning model in the comparison class; and (3) to determine the effect of using the flipped classroom learning model assisted by Google Classroom on the learning outcomes of machining theory. The type of research employed is quasi-experimental. Class A and B students enrolled in the Mechanical Engineering Education Study Program at the Faculty of Engineering, Medan State University, during the even semesters of 2020/21 comprised the population of this study. Researchers used cluster sampling (cluster random sampling) to select two classes from the population and determine the treatment class and comparison class. The data was derived from the results of observations and assessments of learning outcomes. In this study, descriptive and inferential statistical analysis were used to analyze the data. The results of the descriptive statistical analysis indicate that online learning methods result in higher average student learning outcomes (80,05) than traditional learning methods (64,45). On the basis of the results of an inferential statistical analysis, it is possible to conclude that the learning outcomes of machining theory attained by students using the flipped classroom learning model supported by Google Classroom are superior to or have a positive impact on the learning outcomes attained by students using conventional learning models.